Chromosome aberrations [dup(1q)] in endometrial cancer: Gene analysis of 54 surgical specimens in Turkey - Erman Sever; Emek Döğer; Serkan Kumbasar; Bulat Aytek Şık; Muzaffer Temur; Hasan Taylan Yılmaz; Özgür Yılmaz; Pelin Ozun Özbay; İzzet Yücesoy (Elsevier, 2016)
Objective: We aimed to evaluate the frequency of chromosomal aberrations and mutations in the k-ras or Her-2/neu genes in surgical specimens of endometrial carcinoma and their association with clinicopathological findings. Materials and methods: Fifty-four patients who were treated for endometrial cancer between April 2010 and May 2011 at the Kocaeli University Obstetrics and Gynecology Department, Kocaeli, Turkey were enrolled in a prospective study. Clinical and histopathological findings were recorded. Genetic analysis, which included the detection of chromosomal deletions and duplications, as well as k-ras and Her-2/neu mutations, was performed on endometrial samples from surgical specimens. Results: In 70% of cases, tumor size was >2 cm or covered the entire uterine cavity, affecting mostly corpus (76%) and invading less than half of the myometrium (80%). Forty-six cases (86%) had endometrioid-type carcinoma, and early stage (Stage I, 65%) and higher grade (Grade II-III, 66%) tumors were predominant. Lymph node and lymphovascular involvement was positive in 11% and 28% of the patients, respectively. Chromosomal aberrations (deletion or duplication) and Her-2/neu and k-ras mutations were encountered in 44%, 15%, and 13% of surgical specimens, respectively. The most common chromosomal aberration was dup(1q) (n = 16). Oncogenic mutations in Her-2/neu or k-ras had no association with the severity of endometrial cancer, but the presence of chromosomal aberrations, as a whole or dup(1q) alone, were associated with higher tumor size, deeper myometrial invasion, advanced stage or grade, lymphovascular invasion, and lymph node involvement (p < 0.05 for all). Conclusion: Chromosomal aberrations, particularly dup(1q), are related to advanced disease in endometrial cancer. Genetic analysis of cancer tissues may provide important insights in determining disease prognosis.